2006
DOI: 10.1038/sj.embor.7400819
|View full text |Cite
|
Sign up to set email alerts
|

A distinct PAR complex associates physically with VE‐cadherin in vertebrate endothelial cells

Abstract: A cell polarity complex consisting of partitioning defective 3 (PAR‐3), atypical protein kinase C (aPKC) and PAR‐6 has a central role in the development of cell polarity in epithelial cells. In vertebrate epithelial cells, this complex localizes to tight junctions. Here, we provide evidence for the existence of a distinct PAR protein complex in endothelial cells. Both PAR‐3 and PAR‐6 associate directly with the adherens junction protein vascular endothelial cadherin (VE‐cadherin). This association is direct an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 18 publications
5
86
0
1
Order By: Relevance
“…Genetic analysis using Drosophila embryos showed that the Drosophila homolog of Par3 (Bazooka) could establish apical complexes in the absence of AJs, indicating that Bazooka acts upstream of AJ formation (Harris and Peifer 2005). Some reports, on the other hand, suggest the AJs have a physical interaction with these polarity factors: Par3 and Par6, but not aPKC, coprecipitate with VE-cadherin, the endothelial-specific cadherin (Iden et al 2006). Par3/Bazooka colocalizes with cadherins in epithelial junctions (Harris and Peifer 2005;Afonso and Henrique 2006).…”
Section: Interactions With Cell Polarity Regulatorsmentioning
confidence: 99%
“…Genetic analysis using Drosophila embryos showed that the Drosophila homolog of Par3 (Bazooka) could establish apical complexes in the absence of AJs, indicating that Bazooka acts upstream of AJ formation (Harris and Peifer 2005). Some reports, on the other hand, suggest the AJs have a physical interaction with these polarity factors: Par3 and Par6, but not aPKC, coprecipitate with VE-cadherin, the endothelial-specific cadherin (Iden et al 2006). Par3/Bazooka colocalizes with cadherins in epithelial junctions (Harris and Peifer 2005;Afonso and Henrique 2006).…”
Section: Interactions With Cell Polarity Regulatorsmentioning
confidence: 99%
“…It has also been shown that upon loss of one CCM complex component, VE-cadherin and other AJ factors do not correctly localize to the basolateral side of the endothelial membrane but, instead, are diffusely localized on the cell membrane (Lampugnani et al, 2010). Under resting conditions, VE-cadherin interacts and colocalizes with members of the Par polarity complex (consisting of PAR3, PAR6 and protein kinase Cf, PKCf) (Iden et al, 2006;Lampugnani et al, 2010) and is required for the activation of PKCf. Dismantling AJs by inactivation of CCM1 leads to the abrogation of endothelial polarity, which might explain why CCMmediated lesions are abnormally enlarged and present multiple lumens.…”
Section: Mechanisms Of Induction or Inhibition Of Endothelial Permeabmentioning
confidence: 99%
“…Consistent with this data, impaired lumen formation has been reported in zebrafish upon knockdown of expression of the gene encoding VEC (MonteroBalaguer et al, 2009). VEC can directly bind Par3, which is an element of the polarity complex (Iden et al, 2006), and it is required for junctional organization of Tiam (Lampugnani et al, 2002); however, the actual pathway through which VEC regulates endothelial polarity remains unclear.…”
Section: Introductionmentioning
confidence: 99%